Runs of homozygosity reveal past bottlenecks and contemporary inbreeding across diverging populations of an island-colonizing bird ... - Martin, Claudia; Sheppard, Eleanor; Illera, Juan Carlos; Suh, Alexander; Nadachowska-Brzyska, Krystyna; Spurgin, Lewis; Richardson, David (Dryad, 2022)
Genomes retain evidence of the demographic history and evolutionary forces that have shaped populations. Across island systems, contemporary patterns of genetic diversity reflect complex population demography, including colonisation events, bottlenecks, gene flow and genetic drift. Here, we investigate whether island founder events have prolonged effects on genome-wide diversity and runs of homozygosity (ROH) distributions, using whole genome resequencing from six populations across three archipelagos of Berthelot’s pipit (Anthus berthelotii) – a passerine which has undergone island speciation relatively recently. Pairwise sequential Markovian coalescent (PSMC) analyses estimated divergence from its sister species approximately two million years ago. Results indicate that all Berthelot’s pipit populations had shared ancestry until approximately 50,000 years ago, when the Madeiran archipelago populations were founded, while the Selvagens were colonised within the last 8,000 years. We identify extensive long ... : Whole genome data from six populations of Berthelot's pipit across the three archipelagos of their range in the North Atlantic. Resequencing data was generated by mapping Illumina HiSeq reads to a reference genome and calling variants using GATK HaplotypeCaller. ...